Kidney Transplantation after Extended Multivisceral Resection for Pancreatic Ductal Adenocarcinoma. (26th July 2018) - Lapshyn, Hryhoriy; Bolm, Louisa; Nitschke, Martin; Luebke, Andreas M.; Izbicki, Jakob R.; Vashist, Yogesh K.; Keck, Tobias; Wellner, Ulrich F.
Abstract : Long-term survival in patients with pancreatic ductal adenocarcinoma (PDAC) is limited. Consequently, solid organ transplantation in PDAC patients is usually not considered. This is the first case report of kidney transplantation (KT) in a 57-year-old female patient after extended multivisceral resection for PDAC of the distal pancreas who had developed end-stage renal disease (ESRD) due to toxic kidney damage by chemotherapy. 13, 5 years after initial PDAC-operation and 3 years after KT the patient remains in a good general health condition with sufficient function of the kidney allograft without local tumor recurrence or distant metastasis.